1993
DOI: 10.1111/1467-9566.ep11346882
|View full text |Cite
|
Sign up to set email alerts
|

‘They're not the same as us’: midwives' stereotypes of South Asian descent maternity patients

Abstract: The paper examines the stereotypes of South Asian descent women held by midwives in a British hospital. The data are drawn from a small‐scale ethnographic study which investigated the women's maternity experiences. The midwives’ stereotype contained four main themes: the difficulty of communicating with the women; the women's lack of compliance with care and abuse of the service; their tendency to ‘make a fuss about nothing’; and their lack of ‘normal maternal instinct’. The creation, perpetuation and effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
83
1
3

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(91 citation statements)
references
References 20 publications
4
83
1
3
Order By: Relevance
“…In the absence of a back-up counselling service, it would have been wrong to press them (see Kitzinger 1992). Furthermore, Bowler's (1993) work demonstrates, as we have noted, the very strong silencing processes experienced by South Asian women in childbirth. In view of these points, we must caution against assuming that women's reluctance to speak in detail was related to culturally-based modesty; trauma, fear and pain were much stronger themes.…”
Section: Experiences Of Maternity Care: Analysing Data and Reporting supporting
confidence: 69%
See 2 more Smart Citations
“…In the absence of a back-up counselling service, it would have been wrong to press them (see Kitzinger 1992). Furthermore, Bowler's (1993) work demonstrates, as we have noted, the very strong silencing processes experienced by South Asian women in childbirth. In view of these points, we must caution against assuming that women's reluctance to speak in detail was related to culturally-based modesty; trauma, fear and pain were much stronger themes.…”
Section: Experiences Of Maternity Care: Analysing Data and Reporting supporting
confidence: 69%
“…Such people, they suggest, are more than mere interpreters, whose main job, it seems, has been to represent the views of services to the women. Bowler's (1993) important study showed very significant stereotyping of South Asian women by hospital midwives. Her work demonstrates the role of the services in silencing South Asian women particularly clearly: when they cried out in childbirth, their pain was dismissed by midwives as 'a fuss about nothing' (Bowler 1993:166).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Responders in the study of east London specifically cite difficulties experienced in consultations involving interpreters, 7 and there is some evidence that patients' presentation of themselves as knowledgeable, morally responsible individuals is more difficult when patients and providers do not share the same language. [12][13][14] With over 300 languages spoken in London alone and an estimated 300 000 individuals in the UK without functional English to permit communication with a health service provider, 15 it is unsurprising that provision of professional interpreter services in the NHS is both common and costly. 16 Yet there have been no significant published studies involving direct observation of interpreted consultations in the UK, although some work of this sort has been done on consultations with UK patients for whom English is a second language.…”
Section: Introductionmentioning
confidence: 99%
“…Investigating how midwives now ensure culturally sensitive practice for this group is thus especially useful. into account (Bowler 1993 (Pheonix 1990, Caley 1998and Baxter 1996. Fahy (1998) …”
Section: Introductionmentioning
confidence: 99%